The Correlation of Capital Structure, Firm Value, and Size as moderating factor: Capital Structure - Siti Epa Hardiyanti; Akhamdi (PT Larva Wijaya Penerbit, 2022)
This research aimed to investigate wether the profitability and capital structure to the firm value by dividend policy and firm size as moderating variabel in the LQ 45 company listed in Indonesia Stock Exchanged periode 2013-2017. In this research, profitability measured by return on asset, capital structure measured by debt-to-equity ratio, firm value measured by price to book value, dividend policy measured by dividend payout ratio and firm size measured by logaritma natural of totasl asset. The population used in this research is the entire of LQ 45 company listed in Indonesia Stock Exchanged periode 2013-2017. The research sample amounted to 30 companies out of a total population of 73 companies. Sampling used purposive sampling. Data analysis tool used in this research is moderated regression analysis (MRA). The result of this research showed that : (1) Capital structure (DER) is positive signifikan impact on the firm value (2) Firm size negative and not significant impact on the firm value, (3) Firm size can’t moderate the relationship of capital structure with the firm value